The relationship between the boards characteristics and the risk management of the Romanian banking sector - Bunea, Mariana; Dinu, Vasile (Journal of Business Economics and Management, 2020)
The main objective of this research is to analyse the relationship between the board of director’ structure of the banks from the Romanian bank sector, the capital demands and the risk management in what concerns these relationships. Regarding the structure of the board of directors, their size is under the loop, alongside with the education of its members, the gender diversity and the members nationality. The indicators concerning the capital demand that are subject of this research are the solvency and the level of the total own funds of the banks and the ones expressing the risk management are represented by the total exposure of weighted assets according to the risk (RWA), the credit risk exposure, the market risk and the operational risk. The authors have tried to answer the question: Is there or is not a direct relationship between the top of the range board of directors structure and the risk management for the banks from the Romanian bank sector? To answer this question, the used methodology is mainly quantitatively, having as core the deductive statistical analysis, testing and identifying connections from the effect and cause category, considering also the significance level.